La eficacia del medio de control de nulidad electoral como protección de los derechos políticos del ciudadano (2015)
The research exercise aims to establish the effectiveness of the procedural step of the control means of election annulment, for which we proceeded to analyze both the legal norms that regulate as well as the demands of electoral nullity filed before the Council of State against the congressmen elected by popular vote for the legislative period 2014-2018. On this point, the investigation evidenced that there is a high percentage of file lawsuits, which do not thrive claims or simply are not admitted and subsequently rejected, since they are presented without fulfilling requirement and in most cases grounds for annulment is not proven by the plaintiff, which does not mean that the control means of electoral invalidity does not comply with the order, that is, determine the legality of administrative acts of election by popular vote, as it is concluded that the missing is the high level of ignorance of the rule and the process to be followed by the applicant.